1997
DOI: 10.1364/ao.36.003227
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced-fluorescence detection of nitric oxide in high-pressure flames with A–X(0, 2) excitation

Abstract: Laser-induced fluorescence techniques have been used successfully for quantitative two-dimensional measurements of nitric oxide. The commonly applied D-X(0, 1) or A-X(0, 0) schemes are restricted to atmospheric-pressure flames and engines driven with gaseous fuels because of strong attenuation of the exciting laser beam by combustion intermediates. The properties of a detection scheme for which excitation in the nitric oxide A-X(0, 2) band was used were investigated. We discuss the advantages of the A-X(0, 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Different amounts of NO (five different concentrations between 300 and 1400 ppm, laser power density below 7.5 MW/cm 2 ) were doped to the fresh gases, and the related increase in NO-LIF intensity was used for comparison with NO-LIF intensities obtained in the in-cylinder measurements. When transferring the calibration from the atmospheric pressure system to in-cylinder measurements, pressure-dependent effects on line broadening and shifting were included [5,12,13]. A rough calibration can be given for the point where the transmission properties of the burned gases have been assessed with the oxygen-LIF technique shown above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different amounts of NO (five different concentrations between 300 and 1400 ppm, laser power density below 7.5 MW/cm 2 ) were doped to the fresh gases, and the related increase in NO-LIF intensity was used for comparison with NO-LIF intensities obtained in the in-cylinder measurements. When transferring the calibration from the atmospheric pressure system to in-cylinder measurements, pressure-dependent effects on line broadening and shifting were included [5,12,13]. A rough calibration can be given for the point where the transmission properties of the burned gases have been assessed with the oxygen-LIF technique shown above.…”
Section: Resultsmentioning
confidence: 99%
“…By using partially oxygenated fuels (non-sooting fuels), they reported measurements without significant laser attenuation. In previous studies in gasoline IC engines [3,4] and high-pressure flames [5], however, comparisons have shown that excitation at 248 nm (NO A-X(0,2) band) is favorable for IC engine applications. Here, the laser attenuation is minimized, and the possibility of detecting NO-LIF shifted toward shorter wavelengths (emission from the [0,1] vibrational band at 237 nm) strongly discriminates NO-LIF against contribution of interfering LIF caused by hot molecular oxygen [6] and intermediate hydrocarbons [7].…”
Section: Introductionmentioning
confidence: 97%
“…Direct methods have also been reported, including spectroscopic methods (e.g., chemiluminescence) and electrochemical methods [8][9][10][11][12][13]. Among these techniques, electrochemical methods are the most advantageous because they are simple, relatively fast, sensitive, in situ and direct.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the most common type of NO Laser-Induced fluorescence (LIF), at 226 nm, has been extensively examined, including the characterization of radiative lifetimes and quenching4. Its behavior at elevated pressures has been quantified S as well as the performance of LIF at 226 nm versus other methods 6 and excitation frequencies 7 .…”
Section: Introductionmentioning
confidence: 99%